Utilization of Telehealth and Mobile Health in Supporting Healthy Aging in the Elderly: Literature Review - Aris Widiyanto; Rubiyanta; Nicodemus the Ancient Believer (Journal of Health Science Community, 2026)
The increasing elderly population has led to a growing need for effective, accessible, and sustainable healthcare services. Telehealth and mobile health (mHealth) are emerging as part of the digital transformation of healthcare services to support healthy aging in the elderly. This study aims to examine the use of telehealth and mobile health in supporting healthy aging in the elderly. The study used a literature review method by searching articles through the PubMed, Scopus, ScienceDirect, and JMIR Publications databases. Articles were selected based on topic suitability, full-text availability, and research focus related to the use of telehealth and mobile health in the elderly. A total of 8 primary studies that met the inclusion criteria were analyzed in this study. The review results indicate that telehealth and mobile health can improve access to healthcare services, self-management, physical activity, continuity of care, and the involvement of the elderly in self-managing their health. However, the implementation of digital health technology in the elderly still faces obstacles such as low digital literacy, limited internet access, and difficulties in using the technology. Overall, telehealth and mobile health have great potential to support healthy aging through more effective, flexible, and sustainable healthcare services.